2016
DOI: 10.1590/s1677-5538.ibju.2015.0372
|View full text |Cite
|
Sign up to set email alerts
|

Management of full-length complete ureteral avulsion

Abstract: Introduction Complete ureteral avulsion is one of the most serious complications of ureteroscopy. The aim of this report was to look for a good solution to full-length complete ureteral avulsion.Case presentation A 40-year-old man underwent ureteroscopic management. Full-length complete avulsion of ureter occurred during ureteroscopy. Pyeloureterostomy plus greater omentum investment outside the avulsed ureter and ureterovesical anastomosis were performed 6 hours after ureteral avulsion. The patient was follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…In the literature, 55% [17] of 31 cases had avulsion of the right ureter and 45% [14] had it in left ureter. [3][4][5][6][7][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Two of our cases had right ureter avulsion, and one patient had left ureter avulsion which was in line with the literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the literature, 55% [17] of 31 cases had avulsion of the right ureter and 45% [14] had it in left ureter. [3][4][5][6][7][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Two of our cases had right ureter avulsion, and one patient had left ureter avulsion which was in line with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…The literature shows that it is suitable to completely wrap the ureter with omental flap in addition to pyeloureterostomy and ureterovesical anastomosis for all full-length ureteral avulsions and that omental flap feeds the avulsified ureter [5,6]. In line with previous studies and case presentations, we believe that wrapping the avulsified ureter with omental flap and performing pyeloureterostomy and ureterovesical anastomosis would be a good solution for complete ureteral avulsions [27]. We observed that the ureter was relieved on retrograde pyelographies in postoperative patient follow-ups and there was no extravasation in CT urography.…”
Section: Discussionsupporting
confidence: 79%
“…Various definitive management options have been described based upon the type of injury whether one-point or two-point injury, site of injury, and the extent of ureteral loss as well as the condition of the renal unit and that of the patient. The options are ureteropyelostomy [ 20 ], ureteropyelostomy with omental wrapping [ 21 ], end-to-end ureteral anastomosis [ 3 ], uretero-vesical anastomosis with psoas hitch or Boari flap [ 3 , 10 ], transuretero-ureterostomy [ 22 ], appendix interposition of the ureter [ 23 , 24 ], simple repositioning of the completely avulsed ureter [ 6 ], pyeloureterostomy plus greater omentum investment outside the avulsed ureter and uretero-vesical anastomosis [ 25 , 26 ], extended spiral bladder flap [ 20 ], ileal replacement of ureter [ 27 ], and finally nephrectomy [ 9 , 10 , 28 ] and auto renal transplantation [ 29 ]. .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its high success rate, ileal ureter has its own intrinsic risks in the form of mucus secretion and mucus plug formation, associated bowel complications (ileus, bowel obstruction) and anastomotic narrowing and obstructive uropathy, recurrent pyelonephritis, renal calculi, and dyselectrolytemia. In view of all this, the procedure described by Gao et al and Tang et al for complete ureteral avulsion (repositioning of the avulsed ureter by stented uretero-pyelostomy and uretero-vesical anastomosis, followed by omental wrapping of the ureter) appears very attractive [ 25 , 26 ]. If its efficacy is validated by further studies, it may become the preferred option.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, the affected kidney can be mobilized and lowered, which can reduce the anastomosis length by about 3 to 5 cm 11 . In addition, studies have shown a reduction in the incidence of ischemic necrosis by using a pedicled greater omentum graft to cover the bladder flap 12,13 .…”
Section: Surgical Techniquementioning
confidence: 99%